Pediatric Endocrinology A Clinical Handbook - Styne, Dennis M. (Springer International Publishing : Imprint: Springer, 2016)
This text provides a concise, straightforward and clearly written approach for the evaluation of common topics in pediatric endocrinology. Pediatricians, family physicians, residents, fellows and medical students will benefit from the discussion of endocrine physiology and its application to common clinical practice. The text presents the major signs and symptoms and the diagnosis and management of pediatric endocrine disorders. The information presented can prepare a provider for communication with parents of a child with an endocrine condition and may allow the practitioner to avoid an unnecessary consultation. The concepts covered in the text are designed to address the first 10 headings in the content outline of the Sub-board of Pediatric Endocrinology of The American Board of Pediatrics with varying degrees of specificity. The Suggested Reading sections at the conclusion of each chapter direct the reader to outstanding larger and more detailed texts, manuscripts and websites which offer increased detail.